2016
DOI: 10.7554/elife.15104
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids regulate skin pigmentation through nonclassical membrane-bound receptors

Abstract: The association between pregnancy and altered cutaneous pigmentation has been documented for over two millennia, suggesting that sex hormones play a role in regulating epidermal melanocyte (MC) homeostasis. Here we show that physiologic estrogen (17β-estradiol) and progesterone reciprocally regulate melanin synthesis. This is intriguing given that we also show that normal primary human MCs lack classical estrogen or progesterone receptors (ER or PR). Utilizing both genetic and pharmacologic approaches, we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 56 publications
3
103
0
5
Order By: Relevance
“…Consistent with this, we did not detect expression of ER in several melanoma cell lines (Figure 2-figure supplement 1G). In previous work, we demonstrated that GPER was also the sole mediator of estrogen and G-1 effects in normal primary human melanocytes (Natale et al, 2016). To test whether transient GPER signaling induces a persistent state in melanoma cells that affects subsequent tumor growth in vivo, we treated melanoma cells with estrogen, G-1, or vehicle in vitro, and subsequently injected equal numbers of treated cells into host mice ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with this, we did not detect expression of ER in several melanoma cell lines (Figure 2-figure supplement 1G). In previous work, we demonstrated that GPER was also the sole mediator of estrogen and G-1 effects in normal primary human melanocytes (Natale et al, 2016). To test whether transient GPER signaling induces a persistent state in melanoma cells that affects subsequent tumor growth in vivo, we treated melanoma cells with estrogen, G-1, or vehicle in vitro, and subsequently injected equal numbers of treated cells into host mice ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…A pharmacologic approach that recapitulates the female/pregnancy protective effects in men, and women who have not been pregnant, might significantly diminish the overall melanoma burden. Progress in this area has likely been limited by the fact that estrogen effects in melanocytes are not mediated by the well-known nuclear estrogen receptors, but rather through the nonclassical G protein-coupled receptor GPER, which was only recently demonstrated to be expressed in melanocytes (Natale et al, 2016). Here, we demonstrate that this nonclassical estrogen signaling promotes differentiation in melanoma, inhibits tumor cell proliferation, and critically, promotes a phenotype that renders tumors more susceptible to immune-mediated elimination (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations